Avatares de la crítica y de la sátira: HUM® y la Guerra de Malvinas - Mara E. Burkart (Nuevo mundo - Mundos Nuevos, 2013)
The aim of this article is to analyze the impact of Malvinas War and the attitude assumed by HUMOR Registrado (HUM®) magazine during the conflict with England. HUM® was a satire magazine that emerged under the military dictatorship and became an exponent of the cultural and media opposition to the regime. The hypothesis is that at first, the “recovery” of the national sovereignty over the Islands dislocated the political and cultural opposition the military dictatorship that brewed specially in 1981, but that couldn’t silence it. HUM® expressed the initial impact of the surprised “recovery” of the Malvinas Islands and the later reaccommodation that the event generated. The relevance of analyzing HUM® magazine derives from its condition of being a massive media of satire and criticizm. This analysis tries to give an interpretation of the characteristics and limitations of the enunciative and visual fields under the War, and questions the dichotomist views that sustains that since the media under the military dictatorship was massive, then it was an accomplice to it; while if it was underground, it expressed resistance.